Perencanaan Pembangkit Listrik Tenaga Surya Di Perumahan Karyawan Blok B55 PT. Cipta Lestari Sawit Bumirejo Estate - Emidiana, Emidiana; Perawati, Perawati; Rudin, Haidar (Universitas Semarang, 2022)
Housing employees of PT. Cipta Lestari Sawit Bumirejo Estate in block B55 is located in the middle of an oil palm planta- tion, so the state electricity company network cannot reach the housing. So, this housing uses a diesel power plant (PLTD) as a source of electricity, its operational hours are limited and it also causes noise and air pollution. From this problem, one suitable solution is to build a solar power plant (PLTS) that does not cause noise and air pollution and its operating hours can be adjusted as needed. In planning PLTS, there are main components that need to be calculated including Solar Panels, Solar Carger Controller (SCC), Batteries, and Inverters. For planning PLTS in employee housing block B55 PT. Cipta Les- tari Sawit Bumirejo Estate requires 273 solar panels with a capacity of 300 wp per unit, 53 solar charge controllers (SCC) with a capacity of 80 amperes, 34 batteries with a capacity of 2000 Ah per unit, and 68 units with a capacity of 6000 watts per unit. to supply electricity to 70 houses and 8 street lights.